2005
DOI: 10.1007/s00240-005-0498-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral content in calcium renal stone formers

Abstract: Idiopathic renal calcium stone disease often presents with reduced bone mineral content. Investigations using non-invasive methods for the measurement of bone mineral content (single and dual-photon absorptiometry, dual-energy x-ray absorptiometry, quantitative computed tomodensitometry) show a slight decrease in skeletal mineral content of idiopathic renal stone formers (RSFs). The alterations in bone mineral content in RSFs have different explanations: prostaglandin-mediated bone resorption, subtle metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 70 publications
1
23
1
Order By: Relevance
“…First, the tightly regulated conversion of 25(OH)D to 1,25(OH) 2 D by 25-hydroxyvitamin D-1a-hydroxylase (CYP27B1) may have limited synthesis of the active form, thereby preventing excessive intestinal calcium reabsorption. Second, an increase in intestinal calcium reabsorption did occur but did not increase urinary calcium excretion, because the additional calcium was deposited in bone to restore bone mineral content (13).…”
Section: Discussionmentioning
confidence: 99%
“…First, the tightly regulated conversion of 25(OH)D to 1,25(OH) 2 D by 25-hydroxyvitamin D-1a-hydroxylase (CYP27B1) may have limited synthesis of the active form, thereby preventing excessive intestinal calcium reabsorption. Second, an increase in intestinal calcium reabsorption did occur but did not increase urinary calcium excretion, because the additional calcium was deposited in bone to restore bone mineral content (13).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium dietary intake is frequently reduced in stone formers, carrying out a negative calcium balance that contributes to BMD depletion [12,13]. In this context, calcium supplementation remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…First, the presence of hypercalciuria appears to play a relevant role in predisposing to bone demineralization [7][8][9]. Hypercalciuria is associated with important alterations in calcium-phosphate homeostasis [10], persistent overproduction of cytokines predisposing bone loss [11], parathormone (PTH), and calcitriol-mediated pathways [12]. Furthermore, as observed in some studies, subjects with nephrolithiasis may limit their dietary calcium intake, resulting in a negative calcium balance that predisposes the individual to a higher risk of bone loss over time [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…18 In fact, treatment with alkalinizing agents, such as potassium citrate, for 1 year has been shown to significantly increase BMD at the vertebral spine, femoral neck and total hip in postmenopausal woman with osteopenia. 19 Another hypothesis is a defect in vitamin D regulation with either high circulating levels of 1,25 vitamin D or increased bone tissue sensitivity to vitamin D. 20 In the present study, vitamin D stores and VDI were assessed by measuring serum 25(OH) vitamin D levels. There was no significant difference in median serum VD levels between patients with normal and abnormal Z-scores (18.6 vs. 18.8 ng/mL, p = 0.53).…”
Section: Bmd In Urolithiasis Patients With Vitamin D Inadequacymentioning
confidence: 99%
“…Yet others have hypothesized that calcium restriction advice in the past may have contributed to the negative calcium balance since idiopathic renal calcium stone-formers with low BMD have significantly lower calcium intake when compared with calcium stone-formers with normal BMD. [17][18][19][20][21][22] Recently, evidence from the NHANES III study showed that in men with history of urolithiasis, milk consumption was associated more strongly with femoral neck BMD than for men without history of urolithiasis. 5 While patients with osteoporosis are at higher risk of fractures, most (82%) fractures occur in patients with osteopenia.…”
Section: Bmd In Urolithiasis Patients With Vitamin D Inadequacymentioning
confidence: 99%